2017
DOI: 10.1103/physrevc.95.025806
|View full text |Cite
|
Sign up to set email alerts
|

Lower limit on the heat capacity of the neutron star core

Abstract: We show that observations of the core temperature of transiently-accreting neutron stars combined with observations of an accretion outburst give a lower limit to the neutron star core heat capacity. For the neutron stars in the low mass X-ray binaries KS 1731-260, MXB 1659-29, and XTE J1701-462, we show that the lower limit is a factor of a few below the core heat capacity expected if neutrons and protons in the core are paired, so that electrons provide the dominant contribution to the heat capacity. This li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
106
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(111 citation statements)
references
References 63 publications
(146 reference statements)
5
106
0
Order By: Relevance
“…As the present work was in progress, Cumming et al (2016) found that such an amount of energy can raise the core temperature and provides us with a lower limit on its heat capacity that depends on the tantalizing core composition. Comparing with their figure 7, ourT0 2 × 10 7 K provides the strongest constraint to date on the core heat capacity: it must be C > 10 37 (T0/10 8 K) erg K −1 , a value that is close to the minimum provided by the leptons in the core.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the present work was in progress, Cumming et al (2016) found that such an amount of energy can raise the core temperature and provides us with a lower limit on its heat capacity that depends on the tantalizing core composition. Comparing with their figure 7, ourT0 2 × 10 7 K provides the strongest constraint to date on the core heat capacity: it must be C > 10 37 (T0/10 8 K) erg K −1 , a value that is close to the minimum provided by the leptons in the core.…”
Section: Discussionmentioning
confidence: 99%
“…A shallow heat source, with a typical magnitude of Q sh 1 − 2 MeV and one extreme case of Q sh 6−16 MeV per accreted nucleon, has been inferred for several neutron stars although its origin remains unknown (e.g. Brown & Cumming 2009;Degenaar et al 2011a;Deibel et al 2015;Ootes et al 2016;Waterhouse et al 2016). We set ρ sh = 4 × 10 8 g cm…”
Section: Thermal Evolution Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This balance is restored later, during subsequent quiescent states. Observations of the relaxation of such neutron stars combined with observations of an accretion outburst allow one to estimate a lower limit to the heat capacity of the neutron star core [13].…”
Section: Introductionmentioning
confidence: 99%
“…The origin of this shallow heat source is unknown and is important to resolve because the cooling curve can be used to constrain a number of different aspects of crust physics (such as conductivity of the crust and pasta, and the core specific heat; Brown & Cumming 2009;Horowitz et al 2015;Cumming et al 2017). Most systems need ∼1-2 MeV nucleon −1 of shallow heating to explain their cooling curves (e.g., Degenaar et al 2014;Parikh et al 2017;Wijnands et al 2017).…”
Section: Introductionmentioning
confidence: 99%